2011
DOI: 10.3892/ijmm.2011.723
|View full text |Cite
|
Sign up to set email alerts
|

Expression, purification, refolding, and characterization of octreotide-interleukin-2: A chimeric tumor-targeting protein

Abstract: Abstract. The targeting of tumor cells by peptides for drug delivery is a promising strategy for cancer therapy. Interleukin-2 (IL-2), which mediates anti-tumor cellular immune responses, has been approved as a therapy for cancer. However, the serious side effects and short half-life of recombinant IL-2 (rIL-2) has limited its use clinically. Somatostatin receptors (SSTRs), which are expressed in a large number of human tumors, are the targets for in vivo tumor targeting. In this study, we have constructed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The ligand-target SSTR2, chosen for this study, has the potential to enhance potency and minimize undesirable side effects. The studies have shown that the SSTR2 is highly expressed in PDAC cells and tissues, although there may be variations in findings across different studies [21][22][23][24][25][26][27][33][34][35]. This variability could be due to differences in measurement techniques, experimental conditions, or treatment methods with corresponding ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand-target SSTR2, chosen for this study, has the potential to enhance potency and minimize undesirable side effects. The studies have shown that the SSTR2 is highly expressed in PDAC cells and tissues, although there may be variations in findings across different studies [21][22][23][24][25][26][27][33][34][35]. This variability could be due to differences in measurement techniques, experimental conditions, or treatment methods with corresponding ligands.…”
Section: Discussionmentioning
confidence: 99%
“…This targeted approach improves therapeutic outcomes and minimizes damage to healthy cells, reducing the severe side effects typically caused by conventional chemotherapy and radiation. Apart from the markers mentioned above, it has been found that somatostatin receptor 2 (SSTR2) is abundantly expressed in PDAC cells [21][22][23][24][25][26][27]. Hence, it may be an attractive target for the related ligand-somatostatin-and its analogs, such as octreotide and lanreotide (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…More than 200 peptides are in clinical phases, and more than 400 are in advanced preclinical trials [2,3]. Somatostatin is a phylogenetically ancient, multigene family of peptides with two bioactive products, somatostatin-14 and somatostatin-28, acting as both neurotransmitters and neurohormones.…”
Section: Introductionmentioning
confidence: 99%
“…Peptide purification is usually conducted on a commercial column on silica-based reversed phase matrix [14]. 3 There have been important advances in the methodology of peptide purification, and probably the most significant of these is the introduction of reversed-phase high performance liquid chromatography (HPLC). In reversed-phase chromatography, a very broad range of tailor-made stationary phases can be available, which derive from different materials (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is the largest difficulty in the treatment. Somatostatin can combine with somatostatin receptor (SSTR) expressed by tumor cells and then inhibit promoting tumor growth hormone or cytokine's production and adjust tumor blood supply (Hasskarl et al, 2011;Jiang et al, 2011;Zhang et al, 2011;Laznicek et al, 2012;Niu et al, 2012). Insulin-like growth factor-2 (IGF-2) is an important angiogenic factor during the process which HCC induced neovascularization (El Tayebi et al, 2011;Rehem et al, 2011;Wachter et al, 2012 of HCC.…”
Section: Introductionmentioning
confidence: 99%